2012
DOI: 10.1007/978-3-642-31629-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy of Gastroesophageal Junction Cancer

Abstract: Adenocarcinomas of the gastroesophageal junction (GEJ) require multimodal treatment approaches to accomplish good local control and overall survival. While early T1/2 N0 tumors are treated with surgery alone, they are only found in a small subset of patients due to the lack of symptoms at this stage. Most of the tumors are detected in locally advanced stage where surgery alone results in disappointing outcome. Chemotherapy and/or chemoirradiation in the neoadjuvant setting are used to improve conditions for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Many studies confirmed an increasing use of perioperative forms of therapy, due to better survival rates (14)(15)(16)(17)(18)(19)(20)(21). The percentage of our patients received neoadjuvant chemotherapy or chemoradiation or perioperative chemotherapy (25.8%) seems to be low but the number increased remarkably, especially in the last few years.…”
Section: Discussionsupporting
confidence: 58%
“…Many studies confirmed an increasing use of perioperative forms of therapy, due to better survival rates (14)(15)(16)(17)(18)(19)(20)(21). The percentage of our patients received neoadjuvant chemotherapy or chemoradiation or perioperative chemotherapy (25.8%) seems to be low but the number increased remarkably, especially in the last few years.…”
Section: Discussionsupporting
confidence: 58%